Advances in enhancing hydrodeoxygenation selectivity of lignin-derived oxygenates: From synthetic strategies to fundamental techniques - Xinru Wu; Hongwei Zhang; Cejun Hu; Xiaojun Bao; Pei Yuan (Green Energy & Environment, 2025)
In recent years, studies focusing on the conversion of renewable lignin-derived oxygenates (LDOs) have emphasized their potential as alternatives to fossil-based products. However, LDOs, existing as complex aromatic mixtures with diverse oxygen-containing functional groups, pose a challenge as they cannot be easily separated via distillation for direct utilization. A promising solution to this challenge lies in the efficient removal of oxygen-containing functional groups from LDOs through hydrodeoxygenation (HDO), aiming to yield biomass products with singular components. However, the high dissociation energy of the carbon–oxygen bond, coupled with its similarity to the hydrogenation energy of the benzene ring, creates a competition between deoxygenation and benzene ring hydrogenation. Considering hydrogen consumption and lignin properties, the preference is directed towards generating aromatic hydrocarbons rather than saturated components. Thus, the goal is to selectively remove oxygen-containing functional groups while preserving the benzene ring structure. Studies on LDOs conversion have indicated that the design of active components and optimization of reaction conditions play pivotal roles in achieving selective deoxygenation, but a summary of the correlation between these factors and the reaction mechanism is lacking. This review addresses this gap in knowledge by firstly summarizing the various reaction pathways for HDO of LDOs. It explores the impact of catalyst design strategies, including morphology modulation, elemental doping, and surface modification, on the adsorption–desorption dynamics between reactants and catalysts. Secondly, we delve into the application of advanced techniques such as spectroscopic techniques and computational modeling, aiding in uncovering the true active sites in HDO reactions and understanding the interaction of reactive reactants with catalyst surface-interfaces. Additionally, fundamental insights into selective deoxygenation obtained through these techniques are highlighted. Finally, we outline the challenges that lie ahead in the design of highly active and selective HDO catalysts. These challenges include the development of detection tools for reactive species with high activity at low concentrations, the study of reaction medium–catalyst interactions, and the development of theoretical models that more closely approximate real reaction situations. Addressing these challenges will pave the way for the development of efficient and selective HDO catalysts, thus advancing the field of renewable LDOs conversion.